2023
DOI: 10.1073/pnas.2204781120
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining the machine learning life cycle to improve educational outcomes of students

Abstract: Machine learning (ML) techniques are increasingly prevalent in education, from their use in predicting student dropout to assisting in university admissions and facilitating the rise of massive open online courses (MOOCs). Given the rapid growth of these novel uses, there is a pressing need to investigate how ML techniques support long-standing education principles and goals. In this work, we shed light on this complex landscape drawing on qualitative insights from interviews with education experts. These inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Past assessments of the quality of LA research for improving learning has found that evidence of this efficacy is weak (Ferguson & Clow, 2017;Larrabee Sønderlund et al, 2019). Given this, our findings suggest that LA research lacks clear direction toward addressing questions about learning, preferring instead to examine analytical approaches (see also Liu et al, 2022). This focus on examining "things that we can do" instead of "problems that we can solve" has been a chronic obstacle in the nearby field of educational technology research for the past 40 years (Clark, 1983;Reeves & Lin, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…Past assessments of the quality of LA research for improving learning has found that evidence of this efficacy is weak (Ferguson & Clow, 2017;Larrabee Sønderlund et al, 2019). Given this, our findings suggest that LA research lacks clear direction toward addressing questions about learning, preferring instead to examine analytical approaches (see also Liu et al, 2022). This focus on examining "things that we can do" instead of "problems that we can solve" has been a chronic obstacle in the nearby field of educational technology research for the past 40 years (Clark, 1983;Reeves & Lin, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…Although risk prediction has become ubiquitous in education and other domains, its effectiveness for improving outcomes has been called into question. A recent empirical qualitative study by Liu et al (2023) on machine learning applications in education found a significant gap between predictions and beneficent interventions.…”
Section: Introductionmentioning
confidence: 99%
“…"You don't improve things by predicting them better." -Education researcher on the value of predicting academic risk (Liu et al 2023) The study of interventions has been fundamental in the social sciences, statistics, and theoretical computer science (Rosenbaum and Rubin 1983;Pearl 1995;Rubin 2005;Peters, Janzing, and Schölkopf 2017;Hofman et al 2021). The set of techniques and applications for causal inference and analysis is vast, mostly notably including program evaluation and randomized controlled trials (Stephenson and Imrie The Thirty-Eighth AAAI Conference on Artificial Intelligence 1998; Deaton and Cartwright 2018), observational studies (Rosenbaum, Rosenbaum, and Briskman 2010) using modern ML techniques (Athey and Imbens 2016), adaptive trial designs (Collins, Murphy, and Strecher 2007;Montoya et al 2022), individual treatment effect and counterfactual inference (Shalit, Johansson, and Sontag 2017;Lei and Candès 2021;Bynum, Loftus, and Stoyanovich 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9 shows that the AI life cycle is made up of seven stages, which are inception, design and development, verification and validation, deployment, operation and monitoring, re-evaluation, and retirement. These stages are mapped into the ML pipeline cycle in this paper's research framework [58].…”
mentioning
confidence: 99%
“…Figure 9 shows that the AI life cycle is made up of seven stages, which are inception, design and development, verification and validation, deployment, operation and monitoring, re-evaluation, and retirement. These stages are mapped into the ML pipeline cycle in this paper's research framework [58]. ISO/IEC 23053 includes several important aspects that should be considered throughout the AI life cycle and ML pipeline, like risk management, governance, security, privacy, accountability, transparency, explainability, safety, resilience, robustness, and fairness [50].…”
mentioning
confidence: 99%